2010
DOI: 10.1007/s12088-010-0054-5
|View full text |Cite
|
Sign up to set email alerts
|

Fungal isolates from natural pectic substrates for polygalacturonase and multienzyme production

Abstract: Pectin rich wastes and waste dump yard soils were screened and eighty pectinolytic fungal isolates were obtained by enrichment culturing and ruthenium red plate assay. Eight isolates with higher zones of pectin hydrolysis were selected and tested for polygalacturonase production. One isolate identifi ed as Aspergillus awamori MTCC 9166 with highest polygalacturonase activity was tested for utilization of raw pectins for enzyme production. Polygalacturonase production was high in raw pectin sources like Orange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 21 publications
2
19
1
Order By: Relevance
“…The maximum PG activity in this study was nearly nine times higher than the activity obtained by Anuradha et al (16 U ml −1 ) using OP. [24] Moreover, Mohamed et al obtained a maximum PG activity of 10 U ml −1 with Trichoderma harzianum grown on mandarin Citrus reticulata peel as the culture medium, levels lower than the maximum enzyme activity obtained in the current study. [23] On the other hand, Pedrolli et al focused on the production of PG from Aspergillus giganteus by submerged fermentation using agro-industrial wastes such as wheat bran, lemon peel, sugar beet, apple, and orange bagasse.…”
Section: Validationcontrasting
confidence: 65%
See 1 more Smart Citation
“…The maximum PG activity in this study was nearly nine times higher than the activity obtained by Anuradha et al (16 U ml −1 ) using OP. [24] Moreover, Mohamed et al obtained a maximum PG activity of 10 U ml −1 with Trichoderma harzianum grown on mandarin Citrus reticulata peel as the culture medium, levels lower than the maximum enzyme activity obtained in the current study. [23] On the other hand, Pedrolli et al focused on the production of PG from Aspergillus giganteus by submerged fermentation using agro-industrial wastes such as wheat bran, lemon peel, sugar beet, apple, and orange bagasse.…”
Section: Validationcontrasting
confidence: 65%
“…[21] In the literature various agro-industrial wastes including OP and AP have been searched for the PG production for low cost media design. [22][23][24] It is generally agreed that the optimum medium for the enhanced production of PG is that containing pectic materials as an inducer. [25] In the current study, the effects of C source (AP (hyd), AP (hyd) + OP, AP (non-hyd), and AP (non-hyd) + OP), N source (ammonium sulphate and urea), and incubation time (4, 6, and 8 days) were screened in terms of PG activity and biomass.…”
Section: Screening Experimentsmentioning
confidence: 99%
“…Pectic substances are present in the primary cell walls and middle lamellae of many plants and fruits, and they are frequently associated with cellulose, hemicellulose and lignin structures [9]. Their presence in the cell is important for some essential functions: (a) adhesion between cells; (b) mechanical strength of the cell wall; (c) ability to form stabilizing gels; and (d) they play a significant role in the growth of plant cells [10].…”
Section: Structure and Classification Of Pectic Substancesmentioning
confidence: 99%
“…The high degradation rate observed may be attributed to the sufficient enzyme activity aided by suitable bioreactor conditions and the utilisation of Beta vulgaris waste extract which contains soluble sugars, minerals and proteins to support enzyme production. Earlier reports have shown that substrates such as Beta vulgaris have a large content in pectin, reducing sugars, cellulose, and protein (Mulligan 2005;Anuradha et al 2010;Amodu et al 2014). Anuradha et al (2010) showed that Fusarium oxysporum is capable of producing numerous enzymes when grown on Beta vulgaris, orange peel, carrot peel, and pineapple peel.…”
Section: Free Cyanide Degradation Kineticsmentioning
confidence: 99%
“…Fusarium oxysporum has been shown to produce numerous enzymes when grown on Beta vulgaris (Anuradha et al 2010), and this can be investigated under varying cyanide concentrations. The degradation by-products may also be utilised by the microbial species, depending on process conditions.…”
Section: Introductionmentioning
confidence: 99%